2021
DOI: 10.1001/jamaoncol.2020.6353
|View full text |Cite
|
Sign up to set email alerts
|

Association of Osteonecrosis of the Jaw With Zoledronic Acid Treatment for Bone Metastases in Patients With Cancer

Abstract: jaw (ONJ) affects patients with cancer and metastatic bone disease (MBD) treated with bone-modifying agents (BMAs), yet the true incidence is unknown.OBJECTIVE To define the cumulative incidence of ONJ at 3 years in patients receiving zoledronic acid for MBD from any malignant neoplasm.DESIGN, SETTING, AND PARTICIPANTS This multicenter, prospective observational cohort study (SWOG Cancer Research Network S0702) included patients with MBD with either limited or no prior exposure to BMAs and a clinical care plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 22 publications
(33 reference statements)
2
20
0
3
Order By: Relevance
“…Our results are consistent with the earlier findings regarding the risk of ONJ in patients treated with denosumab or zoledronic acid 3‐5,21‐23 . In phase 3 trials among 5723 patients with bone metastases from solid tumors, the ONJ risk was 1.8% with denosumab and 1.3% with zoledronic acid treatment over up to 40 months of follow‐up 3‐5 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results are consistent with the earlier findings regarding the risk of ONJ in patients treated with denosumab or zoledronic acid 3‐5,21‐23 . In phase 3 trials among 5723 patients with bone metastases from solid tumors, the ONJ risk was 1.8% with denosumab and 1.3% with zoledronic acid treatment over up to 40 months of follow‐up 3‐5 .…”
Section: Discussionsupporting
confidence: 91%
“…In an observational cohort study in Belgium with a design similar to our study but without expert ONJ adjudication, the 5‐year incidence proportion of ONJ was 10.0% over a median treatment duration of 18 months among denosumab initiators (51% breast cancer), 6.7% over a median treatment duration of 19 months among zoledronic acid initiators (64% breast cancer), and 15.5% over a median cumulative sequential exposure of 36 months among switchers from zoledronic acid to denosumab (82% breast cancer) 24 . In a cohort study in the United States, the 3‐year cumulative incidence of ONJ was 2.8% for patients with cancer on zoledronic acid and 3.2% among patients with cancer on denosumab 23 . It has been hypothesized that switching from bisphosphonates to denosumab, in addition to being a marker of treatment duration, is itself a risk factor for ONJ 25,26 .…”
Section: Discussionmentioning
confidence: 99%
“…The systematic review by Ottesen et al, 2020, showed that most of the clinical cases of MRONJ described in the literature occurred after tooth extraction, that is, in about 50-70% of cases [14][15][16]. However, the infectious process leading to the extraction of teeth is primary, just like the infection that develops around the implants.…”
Section: Discussionmentioning
confidence: 99%
“…However, emerging data on the development of MRONJ raise new concerns about the duration and cumulative dose of N-BP administration. The cumulative incidence of developing MRONJ among patients receiving intravenous N-BPs increased from 0.5–0.8% at 1 year to 1.3–4.3% at 3 years without a plateau after 2–3 years as reported for patients receiving an alternative antiresorptive drug denosumab [ 1 , 3 ]. The increasingly accumulated N-BPs in the long-term use of N-BPs may be expected in the bone of patients, and the high level released during bone remodelling is considered to increase the risk of developing MRONJ [ 4 6 ].…”
Section: Introductionmentioning
confidence: 99%